2021
DOI: 10.1155/2021/4580949
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Correlation among Sleep Quality, Cognitive Function, and Self-Management Ability in Hospitalized Elderly Patients with Coronary Heart Disease

Abstract: Background. Coronary heart disease (CHD) is the leading cause of death worldwide. The incidence of cardiovascular disease is especially common in low-level and middle-income countries. With the increase in the number of patients with CHD and the complexity of treatment on patients with CHD, many hospitals are devoted to developing new models of care and management for patients with CHD. Understanding the unique characteristics of the patient’s condition, including factors related to self-management, cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
(18 reference statements)
1
2
0
Order By: Relevance
“…Furthermore, this study identified sleep quality as a core factor influencing patients’ self-management behaviours (β=0.387, p<0.001). This finding aligns with a cross-sectional study in elderly patients with coronary heart disease that indicated a positive correlation between sleep quality and self-management ability in patients 36. Sleep deprivation activates brain networks associated with reward, upregulates the gastric hunger/leptin ratio and reduces cognitive control and activity in the cerebral cortex, leading to excessive food consumption and energy imbalance that ultimately affect the patient’s daily lifestyle 37 38.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, this study identified sleep quality as a core factor influencing patients’ self-management behaviours (β=0.387, p<0.001). This finding aligns with a cross-sectional study in elderly patients with coronary heart disease that indicated a positive correlation between sleep quality and self-management ability in patients 36. Sleep deprivation activates brain networks associated with reward, upregulates the gastric hunger/leptin ratio and reduces cognitive control and activity in the cerebral cortex, leading to excessive food consumption and energy imbalance that ultimately affect the patient’s daily lifestyle 37 38.…”
Section: Discussionsupporting
confidence: 87%
“…This finding aligns with a cross-sectional study in elderly patients with coronary heart disease that indicated a positive correlation between sleep quality and self-management ability in patients. 36 Sleep deprivation activates brain networks associated with reward, upregulates the gastric hunger/leptin ratio and reduces cognitive control and activity in the cerebral cortex, leading to excessive food consumption and energy imbalance that ultimately affect the patient's daily lifestyle. 37 38 Moreover, poor sleep quality adversely affects the disease prognosis in patients with NAFLD, with an association between sleep duration and severe steatosis and liver fibrosis showing a negative correlation.…”
Section: Open Accessmentioning
confidence: 99%
“…Breast cancer, as a high incidence tumor in women, can achieve ideal therapeutic effect through surgical treatment, but if effective rehabilitation care cannot be carried out after surgery, it will have adverse effects on postoperative recovery [7]. Therefore, improving the self-care ability of patients is of great significance to improve the prognosis.…”
Section: Discussionmentioning
confidence: 99%